2020
DOI: 10.1080/13501763.2020.1821750
|View full text |Cite
|
Sign up to set email alerts
|

EU agencies’ stakeholder bodies: vehicles of enhanced control, legitimacy or bias?

Abstract: EU agencies are increasingly subject to a flurry of stakeholder bodies. Despite their prevalence, and the considerable variation in structures formally professed to serve the same purpose, we know little about the actor preferences driving the set-up of such structures or the potential implications of specific institutional design choices. We systematically map structural variations across EU agencies and analyse to what extent the establishment and the design of stakeholder bodies is principal-imposed or agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…As research has shown, stakeholder engagement practices often do not yield the balanced engagement or facilitate a voice for the 'public interest' they were intended to do. For instance, in a recent study Busuioc and Jevnaker (2020) find that in the absence of legislator guidance, EU agencies have embraced very different engagement models for their stakeholder committees: some opting for narrow interest representation, while others having attempted to bypass 'thorny' issues of representation altogether by being 'open to all'. Such variation of stakeholder engagement across EU agencies is in line with other studies (Arras & Braun, 2018;Borrás et al, 2007;Perez Duran, 2018) and raises crucial questions as to their eventual effect.…”
Section: Varieties Of Stakeholder Engagement In Regulatory Governancementioning
confidence: 99%
See 3 more Smart Citations
“…As research has shown, stakeholder engagement practices often do not yield the balanced engagement or facilitate a voice for the 'public interest' they were intended to do. For instance, in a recent study Busuioc and Jevnaker (2020) find that in the absence of legislator guidance, EU agencies have embraced very different engagement models for their stakeholder committees: some opting for narrow interest representation, while others having attempted to bypass 'thorny' issues of representation altogether by being 'open to all'. Such variation of stakeholder engagement across EU agencies is in line with other studies (Arras & Braun, 2018;Borrás et al, 2007;Perez Duran, 2018) and raises crucial questions as to their eventual effect.…”
Section: Varieties Of Stakeholder Engagement In Regulatory Governancementioning
confidence: 99%
“…As contributions in this special issue demonstrate, the regulatory state is undergoing a move towards the 'responsive' rather than the 'responsible' regulatory state (Koop & Lodge, 2020), 'a shift away from the model of strictly economic, de-politicised regulation' (Haber & Heims, 2020). This is an emerging feature of the regulatory state diagnosed in this special issue as well as elsewhere: Heims and Lodge (2018), documenting a move towards customer engagement, for instance, speak of a shift to the 'collaborative regulatory state' in the UK context, while Busuioc and Jevnaker (2020) studying EU agency stakeholder committees, diagnose a general shift towards greater politicization in the EU regulatory state: 'Under a combination of legislator-engendered ambiguity and agency-driven initiatives, a whole range of core agency activities and key agency structures have been opened up to societal and interest group input' (Busuioc & Jevnaker, 2020).…”
Section: To What Effect? Diagnosing Key Considerations and Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Customer engagement, stakeholder involvement, and “collaborative regulation” are the noms du jour in regulatory practice (Heims and Lodge 2018). A whole host of bureaucratic agencies in the US and European contexts are found to engage in accountability‐seeking behavior (e.g., Busuioc 2010; Karsten 2015; Koop 2014; Magill 2009; Reiss 2011) as well as a variety of stakeholder engagement and entrepreneurial activities (Arras and Braun 2018; Busuioc and Jevnaker 2020; Braun and Busuioc 2020; Wood 2018). In this context, it becomes increasingly important to study the extent to which these new practices enhance or detract from existing formal controls.…”
Section: Principal Override and Coalitional Driftmentioning
confidence: 99%